PipB2 is a substrate of the Salmonella pathogenicity island 1- encoded type III secretion system - Baisón-Olmo, Fernando; Cardenal Muñoz, Elena; Ramos Morales, Francisco (Elvervier, 2012)
Salmonella harbors two type III secretion systems, T3SS1 and T3SS2, encoded on the pathogenicity islands SPI1 and SPI2, respectively. Several effector proteins are secreted through these systems into the eukaryotic host cells. PipB2 is a T3SS2 effector that contributes to the modulation of kinesin-1 motor complex activity. Here, we show that PipB2 is also a substrate of T3SS1. This result was obtained infecting human epithelial HeLa cells for 2 hours and was confirmed in murine RAW264.7 macrophages, and rat NRK fibroblasts. Analysis at different time points after infection revealed that translocation of PipB2 is T3SS1-dependent in epithelial cells throughout the infection. In contrast, translocation into macrophages is T3SS1-dependent during invasion but T3SS2-dependent at later time points. The N-terminal 10 amino acid residues contain the signal necessary for translocation through both systems. These results confirm the functional overlap between these virulence-related secretion systems and suggest a new role for the effector PipB2
Keywords: Salmonella; Type III secretion; PipB2; Secretion signal; Mammalian cells